Van der Waals Epitaxy of Bismuth‐Based Multiferroic Layered Supercell Oxide Thin Films Integrated on Flexible Mica Substrate - Jianan Shen; Benson Kunhung Tsai; Yizhi Zhang; Ke Xu; James P. Barnard; Zedong Hu; Xinghang Zhang; Haiyan Wang (Small Science, 2024)
Bi2NiMnO6 (BNMO) epitaxial thin films with a layered supercell (LSC) structure have emerged as a promising single‐phase multiferroic material recently. Because of the required strain state for the formation of the LSC structures, most of the previous BNMO films are demonstrated on rigid oxide substrates such as SrTiO3 and LaAlO3. Here, the potential of BNMO films grown on muscovite mica substrates via van der Waals epitaxy, spotlighting their suitability for cutting‐edge flexible device applications is delved. Comprehensive scanning transmission electron microscopy/energy‐dispersive X‐ray analyses reveal a layered structure in the BNMO film and a pristine interface with the mica substrate, indicating high‐quality deposition and minimal interfacial defects. Capitalizing on its unique property of easily cleavable layers due to weak van der Waals forces in mica substrates, flexible BNMO/mica samples are fixed. A standout feature of the BNMO film grown on mica substrate is its consistent multiferroic properties across varied mechanical conditions. A novel technique is introduced for thinning the mica substrate and subsequent transfer of the sample, with post‐transfer analyses validating the preserved structural and magnetic attributes of the film. Overall, this study illuminates the resilient multiferroic properties of BNMO films on mica, offering promising avenues for their integration for next‐generation flexible electronics.